2021
DOI: 10.3233/adr-210302
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Neurofilament Light and Future Declines in Cognition and Function in Alzheimer’s Disease in the FIT-AD Trial

Abstract: Background: Utilities of blood-based biomarkers in Alzheimer’s disease (AD) clinical trials remain unknown. Objective: To evaluate the ability of plasma neurofilament light chain (NfL) to predict future declines in cognition and activities of daily living (ADL) outcomes in 26 older adults with mild-to-moderate AD dementia from the FIT-AD Trial. Methods: Plasma NfL was measured at baseline and 3 and 6 months. Cognition and ADL were assessed using the AD Assessment Scale-Cognition (ADAS-Cog) and AD Uniform Datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The role of NfL as a potential biomarker for AD has been extensively reviewed and recent meta-analysis regarding its association with AD can be found elsewhere (Olsson et al, 2016;Khalil et al, 2018;Bridel et al, 2019;Jin et al, 2019). Recent studies further demonstrated plasma NfL levels or together with cognitive testing as predictors of fast progression (Santangelo et al, 2021) and future declines in cognition and function in AD (Li et al, 2021). Hyperphosphorylation of tau neurofibrillary tangles is one of the hallmarks in AD.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…The role of NfL as a potential biomarker for AD has been extensively reviewed and recent meta-analysis regarding its association with AD can be found elsewhere (Olsson et al, 2016;Khalil et al, 2018;Bridel et al, 2019;Jin et al, 2019). Recent studies further demonstrated plasma NfL levels or together with cognitive testing as predictors of fast progression (Santangelo et al, 2021) and future declines in cognition and function in AD (Li et al, 2021). Hyperphosphorylation of tau neurofibrillary tangles is one of the hallmarks in AD.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…In general, individual plasma biomarkers have shown good accuracy for AD diagnosis, which could be improved by the simultaneous combination of some plasma biomarkers [ 22 , 23 , 24 , 25 ]. The neurofilament light chain (NfL) is another molecule that has been analyzed in the context of AD as a progression biomarker [ 26 ] or predictor for dementia, even more helpful in other pathologies, such as FTLD [ 27 , 28 ]. Different works pointed out the potential use of these biomarkers mentioned, which could change the clinical guides in the following years, with earlier and higher accessible diagnosis [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…NfL indicates subcortical large-caliber axonal degeneration [ 58 , 59 ]. Elevated plasma NfL levels have been established in AD [ 60 , 61 ], correlate to increasing symptom severity in AD [ 62 ], and predicts greater long-term cognitive decline in AD [ 63 65 ]. The positive association between the three T2D indicators and plasma NfL is consistent with existing evidence that used imaging biomarkers of neurodegeneration [ 30 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%